Inhibition of Ubiquitin Specific Protease 1 Sensitizes Colorectal Cancer Cells to DNA-Damaging Chemotherapeutics - Xu, Xin; Li, Shaoyan; Cui, Ximao; Han, Kunkun; Wang, Jun; Hou, Xiaodan; Cui, Long; He, Songbing; Xiao, Jiecheng; Yang, Yili (Frontiers in Oncology, 2019)
Mutations and altered expression of DUBs have been found associated with many human diseases including cancers. In this study, USP1 expression was found significantly increased in some colorectal cancers (CRC). The elevated USP1 level was associated with short overall survival of patients and with advanced stages of cancers. MoreoverIn cultured CRC cells, knockdown of USP1 induced CRC cell growth arrest at G2/M of cell cycle, and reduced the expression of anti-apoptotic proteins Bcl-2 and Mcl-1. WeIts knockdown also led to further demonstrated that inhibiting USP1 decreased the expressionreduction of DNA-repair related substrates FANCD2, and ID1, and PCNA, and reduced cellular anti-apoptotic proteins. Further investigations found that Additionally, the small molecular inhibitor of USP1 ML323 sensitized CRC cells to DNA-targeting chenmotherapeutics, including doxorubicin, TOPI/II inhibitors, and PARP inhibitor, but not that ofto 5-Fu. These results demonstratedindicate that USP1 wasplays a critical in colorectal cancer cell survival, and is a promising target for anti-colorectal cancer chemotherapy. Targeting , and indicated that inhibition of USP1 may is wasrepresent an effective strategy to promising strategy for affectingregulate the DNA-repairing system.